2009
DOI: 10.1097/sap.0b013e318189a9c4
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Ear as a Donor Site For Composite Graft in Nasal Reconstruction

Abstract: Reconstruction of multilayer defects of the lower nose, using composite grafts from the ear is a widespread technique. Little information exists about important aspects of managing the ear as a donor site for composite grafts. In a retrospective study, patient data were worked up concerning special preoperative planning features (donor site, recipient site), defect closure techniques, donor site morbidity, and esthetic and functional long-term results. One hundred ten composite grafts from the auricle were har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The technique for removal of the graft is very simple, leaves no trace and does not cause any residual functional deficit [5,6]. Insertion of the graft is easy and allows rapid solution of surgical problems that would otherwise demand more lengthy reconstruction or the use of microsurgery.…”
Section: Introductionmentioning
confidence: 99%
“…The technique for removal of the graft is very simple, leaves no trace and does not cause any residual functional deficit [5,6]. Insertion of the graft is easy and allows rapid solution of surgical problems that would otherwise demand more lengthy reconstruction or the use of microsurgery.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas some authors, including us, have strongly reported that a graft size exceeding 10 mm is not suitable for reconstruction because of limited blood flow,[ 4 17 18 19 ] there are those who report high success with graft size between 10 and 20 mm[ 20 ] or even up to 25 mm. [ 15 21 ] Grafts exceeding 10 mm may well survive, but the success rate is about 65% for defects approaching 15 mm and <50% for grafts exceeding 15 mm. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Even though, there is no strong evidence to support cooling as a practice to enhance chances of graft survival, majority of authors have advocated its use. [ 9 15 17 24 ] At the same time, quite surprisingly, three series reporting high success with large sized composite grafts did not resort to cooling. [ 20 21 25 ] We feel this practice could be justified on the analogy of ‘warm ischemia time’ for a replantation, and is recommended by us if ambient temperatures are high, as is often the case in our country.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations